EXAMINATION OF EATING ATTITUDE, EATING AWARENESS AND SOCIAL APPEARANCE ANXIETY OF UNIVERSITY STUDENTS - Çakaroğlu, Deniz; Ömür, Esra Hafıza; Arslan, Cengiz (Nigde Omer Halisdemir University, 2020)
This study seeks to examine eating attitude, eating awareness and social appearance anxiety of university students. A total of 362 students aged 18-31 participated in the study. The average age of them was identified as 22 519 ± 2.60 years. Participants were subjected to Eating Attitude Test (EAT-40), Eating Awareness Scale-30 (EAS-30), Social Appearance Anxiety Scale (SAAS). Statistical analyses were evaluated in SPSS program where levels of significance were taken as p

Bu çalışma üniversitede öğrenim gören öğrencilerin; yeme tutumu, yeme farkındalığı ve sosyal görünüş kaygısının değerlendirilmesi amacıyla yapılmıştır. Araştırmaya 18-31 yaş arası toplam 362 öğrenci katılmıştır. Öğrencilerin yaş ortalaması 22.519 ± 2.60 yıl olarak belirlenmiştir. Katımcılara Yeme Tutumu Testi (YTT-40), Yeme Farkındalığı Ölçeği-30 (YFÖ-30) ve Sosyal Görünüş Kaygısı Ölçeği (SGKÖ) uygulanmıştır. İstatistik analizler SPSS programında anlamlılık düzeyleri p
ÜNİVERSİTE ÖĞRENCİLERİNİN YEME TUTUMU, YEME FARKINDALIĞI VE SOSYAL GÖRÜNÜŞ KAYGISININ DEĞERLENDİRİLMESİ
Keywords: Sports Medicine; Spor Hekimliği